PERBEDAAN REAKSI PASAR DAN KINERJA AKUNTANSI PERUSAHAAN PROSPECTOR DAN DEFENDER: ANALISIS DENGAN PENDEKATAN LIFE CYCLE THEORY - Anis Dwiatmajanti; Nur Cahyonowati (Diponegoro Journal of Accounting, 2013)
Prospector and defender are two different types of extreme strategies.Habbe and Hartono (2001) and Saraswati and Atmini (2007) suggested on the differences in accounting performance and market reaction of prospector and defender. Earnings growth, sales growth, dividend payout ratio, return on investment and the market reaction are variables that is used to determine the implications of the organizational strategy, i.e.This study discusses the differences in accounting performance and market reaction of prospector and defender firms from 2006-2010. This research adds return on investment (ROI) as new measurement of accounting performance.Selecting of prospector and defender firms is determined using four variables,  the ratio of the number of employees to total net sales, the ratio of price to book value, the ratio of capital to total assets, and the ratio of capital expenditure to market value of equity. Four proxies of this research is analyzed by Common Factor Analysis. Sample of this study consisted of 20 companies, each 10  companies categorized as a prospector and defender. Life cycle theory is used to analyze the differences in accounting performance measurement prospector and defender. Data were analyzed using T-Test and Mann-Whitney U-Test. The results of the study showed that there was no difference in earnings growth, return on investment, and market reactions between companies prospector and defender firms. On the contrary, the company's sales growth and dividend payout ratio of defender firms is higher than the prospector firms.